2020
DOI: 10.1016/j.biopsych.2019.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Dysfunction in Human Neurons With Autism-Associated Deletions in PTCHD1-AS

Abstract: BACKGROUND: The Xp22.11 locus that encompasses PTCHD1, DDX53, and the long noncoding RNA PTCHD1-AS is frequently disrupted in male subjects with autism spectrum disorder (ASD), but the functional consequences of these genetic risk factors for ASD are unknown. METHODS: To evaluate the functional consequences of PTCHD1 locus deletions, we generated induced pluripotent stem cells (iPSCs) from unaffected control subjects and 3 subjects with ASD with microdeletions affecting PTCHD1-AS/PTCHD1, PTCHD1-AS/DDX53, or PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 61 publications
4
58
1
1
Order By: Relevance
“…Additionally, in contrast to the findings with SHANK3, SHANK2 loss of function mutations led to an increase in the number of synapses, as well as in the complexity of the dendritic tree [146]. Individuals with NLGN4 [138] and one individual with a PTCHD1-AS mutation [140] also showed an increase in the number of synapses.…”
Section: Neuronal Differentiation and Morphologycontrasting
confidence: 63%
See 3 more Smart Citations
“…Additionally, in contrast to the findings with SHANK3, SHANK2 loss of function mutations led to an increase in the number of synapses, as well as in the complexity of the dendritic tree [146]. Individuals with NLGN4 [138] and one individual with a PTCHD1-AS mutation [140] also showed an increase in the number of synapses.…”
Section: Neuronal Differentiation and Morphologycontrasting
confidence: 63%
“…Conversely, genetically defined forms of ASD, mutation in NRXN1, and 22q11.2 deletion showed evidence of a decreased proliferation rate [124,135,144]. However, it is important to note that not all studies that examined cell cycle found changes in ASD [116,125,140,143]. The acceleration in cell cycle in idiopathic ASD supports a finding from toddlers with ASD in which cell cycle gene networks were positively correlated with brain volume [155].…”
Section: Cell Cycle and Proliferationmentioning
confidence: 74%
See 2 more Smart Citations
“…Alterations in GABAergic neurotransmission are implicated in ASD affectation and may result from disruptions of synaptic development, resulting in imbalanced excitatory and inhibitory neuronal activity (39,48). Since most in vitro modeling studies characterize neurodevelopmental phenotypes only in excitatory neurons (10,19,49,50), the extent to which GABAergic inhibitory neurodevelopment is affected in iPSC models of ASD remains largely unexplored. This work suggests that assessing phenotypes in both excitatory and inhibitory neurons may be beneficial for identifying such neuronal cell type-specific alterations of neurodevelopment that may contribute to ASD.…”
Section: Discussionmentioning
confidence: 99%